Utilization of Solar Energy As An Environmentally Friendly Source of Electricity In Karang Taruna, Gambir District - Widia Yanti; Reno Pratiwi; Prayang Sunny Yulia; Fadliah Fadliah; Pauhesti Pauhesti; Faiz Rohman; M. Khair Dabit Istibra (International Journal Of Community Service, 2025)
This community service program titled "Socialization and Training on the Utilization of Solar Energy as an Environmentally Friendly Electricity Source in Karang Taruna, Gambir District" aimed to address the critical issues faced by the community due to their heavy reliance on unstable and costly fossil energy from PLN (the state-owned electricity company). The program also targeted the low understanding and practical skills related to solar energy and the underutilization of solar energy potential in urban settings. The implementation comprised two core components: socialization of solar energy and climate change impacts, and hands-on training on mini solar panel systems. Using interactive lectures, demonstrations, direct practices, and discussions, the program was conducted on March 16, 2025, involving 31 participants mainly from Karang Taruna members. A significant improvement in participants’ comprehension was observed, with average pre-test scores rising from 45 to 82, indicating an 82.22% increase. Furthermore, participant satisfaction reached 90.32%, alongside a 70.96% enhancement in practical ability to operate mini solar panel setups. Key outputs included teaching materials, posters, and scientific articles, collectively contributing toward enhanced community energy independence, reduced electricity costs, and promotion of clean energy adoption in urban areas.